IoT-Based Real-Time Monitoring System for Temperature and Humidity Control in Pharmaceutical Manufacturing - Khandve Pranjal Mahendra; Kolhe Payal Ganpat; Kshirsagar Vedant Umesh; Lokhande Sai Sunil; Naveen Kumar (International Journal of Mobile Computing Technology, 2026)
Environmental conditions, especially temperature and humidity, play a vital role in pharmaceutical manufacturing processes. Even minor fluctuations in these parameters can significantly influence the stability, potency, and overall effectiveness of drug formulations. In many cases, uncontrolled environmental variations may lead to chemical degradation, reduced shelf life, contamination risks, and substantial financial losses for manufacturers. Therefore, maintaining precise and consistent environmental conditions is essential to ensure product quality, regulatory compliance, and patient safety. To overcome these challenges, an Internet of Things (IoT) based real-time monitoring system has been designed to continuously observe and regulate temperature and humidity levels within pharmaceutical production facilities. The proposed system incorporates DHT22 sensors to accurately measure environmental conditions and an ESP32 microcontroller to process, analyze, and transmit the collected data. The processed information is displayed through a user-friendly mobile application developed using MIT App Inventor, allowing operators to monitor real-time readings remotely and conveniently. Additionally, the system is programmed with predefined safety thresholds. Whenever the measured temperature or humidity values exceed acceptable limits, immediate alerts are generated to notify responsible personnel. This enables prompt corrective actions to prevent product damage and maintain optimal manufacturing conditions. Overall, this smart monitoring solution improves quality assurance, minimizes product wastage, enhances operational efficiency, and offers a reliable, affordable approach to environmental control in pharmaceutical industries
Keywords: DHT22 sensor; ESP32; Humidity monitoring; IOT; MIT App Inventor; Temperature control; drug stability; pharmaceutical manufacturing; quality assurance; real-time monitoring